Obtenção de scaffold compósito com deposição de nanopartículas de cério e tratamento superficial para aplicação em engenharia de tecido - Oliveira, Ítalo de Matos (Universidade Federal de São Carlos, 2025)
Biodegradable scaffolds manufactured via additive manufacturing are promising for bone regeneration as they mimic the natural extracellular matrix of bone, both in terms of architecture and biochemical and mechanical properties. They act as temporary templates, guiding bone tissue growth, accelerating the recovery of patients with orthopedic trauma, and reducing the need for multiple surgeries. This study investigated the surface modification of poly(lactic acid) (PLA)-β-tricalcium phosphate (β-TCP) composite scaffolds (90:10 wt/wt%) produced by additive manufacturing, using plasma treatment, alkaline hydrolysis, and deposition of cerium oxide nanoparticles (CeONPs) to stimulate bone cell growth. PLA-β-TCP filaments were obtained by extrusion and used to fabricate the scaffolds via 3D printing. The surfaces were treated with plasma or sodium hydroxide, followed by deposition of CeONPs, either synthesized or commercially acquired. The nanoparticle synthesis was monitored by UV-Vis spectroscopy, with an absorbance peak at 270 nm, indicating particles with a radius of approximately 20.5 nm. The scaffolds were evaluated for mechanical properties (uniaxial compression), surface characteristics (contact angle, Atomic Force Microscopy – AFM, Scanning Electron Microscopy – SEM), and cell viability (Alamar Blue assay). The results showed that the scaffolds exhibited elastic moduli (78-127 MPa) within the range of native human bone. Contact angle measurements revealed increased hydrophilicity after alkaline treatment and reduced hydrophilicity after CeONP addition. AFM and SEM analyses showed differences in roughness and surface morphology (presence of pores), with the NaOH and synthesized CeONP group being the roughest. In pre-osteoblastic mouse cell (MC3T3-E1) assays, the sample treated with plasma and commercial CeONPs showed the highest cell proliferation. The results highlight the positive effect of surface treatments on scaffold functionalization and the increased bioactivity of the material with CeONP deposition.
Development of a composite scaffold with Cerium nanoparticle deposition and surface modification for applications in tissue engineering
Keywords: Scaffold; Manufatura aditiva; Compósito; Biomaterial; Engenharia de tecido ósseo; Nanopartículas de óxido de cério; Additive manufacturing; Composite; Bone tissue engineering; Cerium oxide nanoparticles; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::MATERIAIS NAO METALICOS